A formative assessment model of critical thinking in mathematics learning in junior high school - R Rosnawati; Badrun Kartowagiran; Jailani Jailani (REID (Research and Evaluation in Education), 2015)
This study aims to obtain a valid and reliable formative evaluation model of critical thinking. The method used in this research was the research and development by integrating Borg Gall's model and  Plomp's development model. The ten steps Borg Gall’s model were modified into five stages as the stages in the Plomp's model. The subjects in this study were 1,446 students of junior high schools in DIY, 14 mathematics teacher, and six experts. The content validity employed was expert judgment, the empirical validity and reliability used were loading factor, item analysis used PCM 1PL, and the relationship between disposition and critical thinking skill used was structural equation modeling (SEM). The developed formative evaluation model is the procedural model. There are five aspects of critical thinking skill: mathematic reasoning, interpretation, analysis, evaluation, and inference, which entirely composed of 42 items. The validity of the critical thinking skill instruments achieves a significance degree as indicated by the lowest and the highest loading factors of 0.38 and 0.74 subsequently, the reliability of every aspect in a good category. The average level of difficulty is 0.00 with the standard deviation of 0.45 which is in a good category. The peer assessment questionnaire of critical thinking disposition consists of seven aspects: truth-seeking, open-minded, analysis, systematic, self-confidence, inquisitiveness, and maturity with 23 items. The critical thinking disposition validity achieves the significance degree as indicated by the lowest and the high factor loading of 0.66 and 0.76 subsequently, and the reliability of every aspect in a good category. Based on the analysis of the structural equation model, the model fits the data.